An application note to An engineering guide to seismic risk to dams in the United Kingdom (Thomas Telford, 1998)
This application note aims to add to the guide and to improve consistency in applying it. Technical developments since publication of the guide are identified and some implications of analyses already carried out on British dams are examined.